1937
DOI: 10.1002/zaac.19372320108
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis des Calciumcarbides. II. Über die Darstellung von reinem Calciumcarbid und die Auffindung einer dritten kristallisierten Phase des Calciumcarbides

Abstract: 1. Es wird ein nahezu reines (99,2%, iges) weißes Calciumcarbid, das außer Spuren von CaO und Kohlenstoff keine Verunreinigungen enthielt, erstmalig dargestellt durch Erhitzen von reinem Calciumcyanamid mit und ohne Kohlenstoff (Umkehrung der Azotierreaktion).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
1

Year Published

1942
1942
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…However, another unexpected observation was made: The diffraction patterns of the pulverized samples invariably now showed the lines of carbide II exclusively. 1 This was in conspicuous disagreement with the previous results (6,7), according to which carbide II was to be obtained in the presence of calcium cyanamide only. In these latest experiments, however, the nitrogen was carefully prevented from entering the carbide melt; accordingly, the analysis of the pulverized product showed that only 0.05-0.10 per cent of nitrogen was present.…”
contrasting
confidence: 69%
See 4 more Smart Citations
“…However, another unexpected observation was made: The diffraction patterns of the pulverized samples invariably now showed the lines of carbide II exclusively. 1 This was in conspicuous disagreement with the previous results (6,7), according to which carbide II was to be obtained in the presence of calcium cyanamide only. In these latest experiments, however, the nitrogen was carefully prevented from entering the carbide melt; accordingly, the analysis of the pulverized product showed that only 0.05-0.10 per cent of nitrogen was present.…”
contrasting
confidence: 69%
“…Especially the spot corresponding to an interplanar spacing of 2.85Á., on the equator of the diagram,-by far the strongest reflection,-could in no way be interpreted as a reflection from phase II. Furthermore, it corresponded perfectly to the strongest line of the powder pattern of phase III (7), and the remaining reflections, which could not be ascribed to phase II, corresponded entirely satisfactorily to the lines of the powder x-ray pattern of phase III. The conclusion was to be drawn from these results that the carbide, made in the electric-arc furnace under the described precautions, originally had structure III, as expected, but had changed its crystal lattice, during the process of grinding in the mortar,-that is, by mechanical deformation,-into that of carbide II.…”
mentioning
confidence: 63%
See 3 more Smart Citations